2014
DOI: 10.5194/tc-8-547-2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of snow depth distribution on surface roughness in alpine terrain: a multi-scale approach

Abstract: Abstract. In alpine terrain, the snow-covered winter surface deviates from its underlying summer terrain due to the progressive smoothing caused by snow accumulation. Terrain smoothing is believed to be an important factor in avalanche formation and avalanche dynamics, and it affects surface heat transfer, energy balance as well as snow depth distribution. To assess the effect of snow on terrain, we use an adequate roughness definition. We developed a method to quantify terrain smoothing by combining roughness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…However, for very strong and thick slabs, the column length should not be lower than 2 m in order to be able to still observe a possible arrest of the fracture due to slab tensile failure. If slab fracture is not observed in a PST for a column length of 2 m, fracture arrest is likely to be mainly driven by terrain and snowpack spatial variability and a 3D-terrain model including the snowpack might be required to evaluate where fracture arrest might occur (Veitinger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, for very strong and thick slabs, the column length should not be lower than 2 m in order to be able to still observe a possible arrest of the fracture due to slab tensile failure. If slab fracture is not observed in a PST for a column length of 2 m, fracture arrest is likely to be mainly driven by terrain and snowpack spatial variability and a 3D-terrain model including the snowpack might be required to evaluate where fracture arrest might occur (Veitinger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that this may lead to a more uniform slab thickness and, in combination with reduced support from the bed surface, to potentially larger release area sizes -in particular for surface slabs (McClung, 2001;Simenhois and Birkeland, 2008). Further, Veitinger et al (2014) showed that the progressive smoothing of surface roughness can be captured by a multi-scale roughness parameter. So far, roughness is only incorporated in some approaches as a single-scale terrain parameter, often not reflecting the adequate scale of a given snow scenario.…”
Section: Terrain-snow Cover Interactionmentioning
confidence: 99%
“…In a shallow snowpack, terrain roughness can have a stabilising function, hindering the formation of continuous weak layers (Schweizer et al, 2003), as well as providing mechanical support to the snowpack (McClung, 2001). However, increasing snow accumulation is known to smooth out surface roughness (Veitinger et al, 2014), reducing snowpack variability in the surface layers (Mott et al, 2010) and the mechanical support of a slab (van Herwijnen and Heierli, 2009). In this case, the stabilising effects of terrain roughness disappear or even reverse (McClung and Schaerer, 2002), and the formation of continuous weak layers and slabs, which favours fracture propagation (Simenhois and Birkeland, 2008), is facilitated.…”
Section: Roughnessmentioning
confidence: 99%
See 2 more Smart Citations